Enhanced Wide‐Angle Energy Conversion Using Structure‐Tunable Waveguide Arrays as Encapsulation Materials for Silicon Solar Cells (Phys. Status Solidi A 2∕2019). Issue 2 (23rd January 2019) - Biria, Saeid; Chen, Fu‐Hao; Hosein, Ian D.
Abstract : Silicon Solar Cells Broadband waveguide arrays created in the protective transparent encapsulant of a solar cell enable the collection of solar light over a wide angular window, thereby offering the potential to sustain conversion efficiency and performance over the course of the day and across seasons. More details can be found in article number1800716 by Saeid Biria, Fu‐Hao Chen, and Ian D. Hosein.